2009
DOI: 10.1016/j.jtcvs.2008.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump versus on-pump myocardial revascularization in patients with ST-segment elevation myocardial infarction: A randomized trial

Abstract: Off-pump surgery reduced early mortality and morbidity in patients with ST-segment elevation myocardial infarction in respect to the conventional procedure. Off-pump surgery showed better results than on-pump surgery in patients who underwent surgery within 6 hours from the onset of symptoms and in patients with cardiogenic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 25 publications
3
49
0
2
Order By: Relevance
“…In the same meta-analysis (3) there was no difference in atrial fibrillation rates between off-pump versus on-pump, contrary to a smaller, previous meta-analysis of RCTs (37) ( Table 8). (14) while the late mortality did not differ compared to conventional surgery (42). Several retrospective studies found a benefit in using off-pump techniques in other high risk groups such as: females (43) or reoperative coronary artery bypass grafting (44).…”
Section: Postoperative Renal Dysfunctionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the same meta-analysis (3) there was no difference in atrial fibrillation rates between off-pump versus on-pump, contrary to a smaller, previous meta-analysis of RCTs (37) ( Table 8). (14) while the late mortality did not differ compared to conventional surgery (42). Several retrospective studies found a benefit in using off-pump techniques in other high risk groups such as: females (43) or reoperative coronary artery bypass grafting (44).…”
Section: Postoperative Renal Dysfunctionmentioning
confidence: 93%
“…One small sample size RCT by Fattouch et al showed a reduced mortality in patients with ST elevation undergoing urgent/emergent off-pump coronary surgery compared to on-pump surgery (14). Deppe et al in meta-analysis of RCTs on almost 16,900 patients found no difference in 30-day mortality.…”
Section: Operative Mortalitymentioning
confidence: 99%
“…Hence, the complications of the most complicated OPCAB-procedures were exported to the CCABG-group. It is worth noting that one of the few randomized studies that specifically included high-risk patients who received an acute operation, found a significantly higher mortality in the CCABG group than in the OPCAB group (7.7% vs. 1.6%, p=0.04) (32). However, this study exclusively included patients who only needed grafting the LAD territory, which would be expected to favour OPCAB.…”
Section: Periperative Mortalitymentioning
confidence: 83%
“…However, many randomized studies provide evidence of a lower, subclinical release of biochemical markers of myocardial damage among patient operated using OPCAB (12,25,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). This tendency is very robust across the different studies, and it is even preset in a study that showed a significantly higher proportion of graft occlusions in the OPCAB group (25).…”
Section: Myocardial Damagementioning
confidence: 97%
See 1 more Smart Citation